Analisis Penerapan Pajak Hotel, Pajak Restroran, Pajak Bumi dan Bangunan Terhadap Pendapatan Asli Daerah Kota Pagaralam - Agustra, Rizan; Saladin, Hendry; Sudiyanto, Totok (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study aims to determine the Contribution of Hotel Tax, Restaurant Tax, Land and Building Tax to the Local Original Revenue (PAD) of Pagaralam City Government and is expected to know about regional finance, especially about Regional Original Revenue (PAD). The population of this study is the financial statements of local tax realization. The data consists of Hotel, Restaurant Tax, Land and Building Tax (PBB), and Original Blood Income. The sample taken is in the form of data in the form of targets and reports on the realization of hotel tax, restaurant tax, land and building tax and local original income during the research period (2020-2023). The results of research and discussions that have been carried out conclude that the Effectiveness of Hotel Tax in Pagaralam City in 2020-2022 is 109.54% categorized as very effective. The effectiveness of Restaurant Tax in Pagaralam City in 2020-2022 is 119.41% very effective. The effectiveness of the Land and Building Tax in Pagaralam City in 2020-2022 is 109.85% very effective. Meanwhile, based on the results of the analysis of Regional Tax Contributions, the average percentage of Regional Tax Contributions to Regional Original Revenue in 2020-2022 is 18.38%, which is included in the poor category. So based on the criteria or indicators of effectiveness and contribution, it can be said that the effectiveness of Hotel Tax, Restaurant Tax, Land and Building Tax in Pagaralam City is categorized as very effective, and the contribution of local tax in Pagaralam City is categorized as not good so that it shows that the Regional Finance Agency of Pagaralam City is very effective in managing Regional Tax, but the Regional Finance Agency of Pagaralam City needs to improve its performance to boost revenue in order to contribute through local taxes.